Frequency of Helicobacter Pylori (H. Pylori) among Patients presenting with Duodenal Perforation - Muhammad Alam, Rizmi Tahir, Siddique Ahmad, Sheema Amin, Amir Zareen, Ali Gohar Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of helicobacter pylori among patients presenting with duodenal perforation. Study design: Descriptive cross-sectional study. Place and duration of study: General Surgery Department Hayatabad Medical Complex Peshawar from 1st March 2021 to 30th September 2021 Methodology: One hundred and seventy five patients who had a first-time duodenal perforation, were between the ages of 20 and 60, and had a prior history of peptic ulcer disease lasting at least six months were included. Results: Thirty three (18.8%) patients had H pylori in body mass index of 18.5-24.9kg/m2, 39(22.3%) in BMI 24.9-29.9kg/m2 and 19(10.8%) in BMI 30-32.2 kg/m2. Fifty nine (33.7%) patients had H. Pylori who had peptic ulcer disease (PUC) since 7-11 years and 32(18.36%) had the condition with PUC 11-15 years. 69(39.4%) belongs to Urban areas, while 22(12.6%) belongs to rural areas. 18(10.3%) patients found to be chain smoker, while diabetes mellitus and hypertension was noted in 15(8.6%) Conclusion: Our population frequently develops duodenal perforation from H. Pylori owing to peptic ulcer disease. It is a serious problem and we advise more study to identify risk factors linked to this high H. Pylori burden and preventive measures to stop its spread and the morbidity linked to it. Key Words: Helicobacter pylori, Duodenal ulcer, Gastric ulcer, Peptic ulcer, Perforated peptic ulcer, ELISA